Statement by the President of the Bolivarian Republic of Venezuela, Hugo Chávez, at the LXI General Assembly of the United Nations Organization - de Venezuela, Hugo Chávez, Presidente de la República Bolivariana (2016)
Statement by the President of the Bolivarian Republic of Venezuela, Hugo Chávez, at the LXI General Assembly of the United Nations Organization (UN), United Nations headquarters, New York Wednesday, September 20, 2006.